UJI HIPOTESIS PADA HASIL PEMANFAATAN PEMETAAN SMA (STUDI KASUS KAB. KARANGANYAR) - Mafazan, Mukhamad Richo; Sumarsono, Sumarsono; Retnowati, Nurcahyani Dewi (Compiler, 2014)
The lack of information in the area Karanganyar especially the schools are the usual information accessible online . In the era of information technology , as now, it should be information about the school ,information about the schools that are managed and published through the Internet . Some existing sites and information support the schools in the area tends to be static . The information displayed tended outdated information and even out -of -date , not updated in quite a long period of time . Then create a mapping application Senior High School Case Study Karangnyar District . With the application of Mapping Mash-up Senior High School In Karanganyar , the user can see the schools without having to come to school to see school information desired . To make the application Mapping Mash-up Senior High School In Karanganyar JSON format which utilizes lighter and then made accessible to the web service . Results of experiments performed as expected ie when the user opens a web service can simply select senior high school or vocational high school category and public or private category so people can see the information on each school were selected.